Thinking Disposition Profile of Class XI IPA Students in a Palembang School - Rahmawati Rahmawati; Diana Rochintaniawati (ISEJ : Indonesian Science Education Journal, 2021)
This study aims to determine to find out how far students' critical thinking skills are. Through the description above, the researcher plans to determine the critical disposition ability profile of students in one of the schools in Palembang. This research was conducted in one of the schools in Palembang. The total sample is 70 people. The instruments used in this research are Critical Thinking Disposition Test and Critical Thinking Ability test. Data analysis using SPSS version 22 software application. The critical thinking ability of high school students in biology learning is still low, because the average value obtained is still less than the KKM. Meanwhile, the students' critical disposition ability is thickly proportional, because the average value obtained is in the good category. Based on these results, it was found that there was no relationship between critical thinking skills and critical disposition because there was no association between the two.